A Plasmid System That Utilises Phosphoribosylanthranilate Isomerase to Select Against Cells Expressing Truncated Proteins - Aditi A. Ghuge; Susanne Gottfried; Anja H. Schiemann; Evelyn Sattlegger (Biomolecules)
We have generated a vector that enables the removal of plasmids coding for truncated proteins. This vector expresses a protein of interest in the yeast Saccharomyces cerevisiae from a galactose-inducible promoter. The gene of interest is fused in-frame to a downstream sequence coding for phosphoribosylanthranilate isomerase (PRAI), which catalyses the third step in tryptophan biosynthesis. As a consequence, only the full-length protein of interest renders the host cell tryptophan prototrophic, allowing for selection against cells expressing truncated proteins. Our proof-of-principle study demonstrates that PRAI is functional when fused C-terminally to a protein, robustly rendering cells tryptophan prototrophic. The N-terminal GST tag and C-terminal myc tag allow for tag-mediated protein purification, co-precipitation studies, determination of relative expression levels, as well as validation of full-length expression of the protein via Western blotting.